Genome Editing of the CYP1A1 Locus in iPSCs as a Platform to Map AHR Expression throughout Human Development - Brenden W. Smith; Elizabeth A. Stanford; David H. Sherr; George J. Murphy (Stem Cells International)
The aryl hydrocarbon receptor (AHR) is a ligand activated transcription factor that increases the expression of detoxifying enzymes upon ligand stimulation. Recent studies now suggest that novel endogenous roles of the AHR exist throughout development. In an effort to create an optimized model system for the study of AHR signaling in several cellular lineages, we have employed a CRISPR/CAS9 genome editing strategy in induced pluripotent stem cells (iPSCs) to incorporate a reporter cassette at the transcription start site of one of its canonical targets, cytochrome P450 1A1 (CYP1A1). This cell line faithfully reports on CYP1A1 expression, with luciferase levels as its functional readout, when treated with an endogenous AHR ligand (FICZ) at escalating doses. iPSC-derived fibroblast-like cells respond to acute exposure to environmental and endogenous AHR ligands, and iPSC-derived hepatocytes increase CYP1A1 in a similar manner to primary hepatocytes. This cell line is an important innovation that can be used to map AHR activity in discrete cellular subsets throughout developmental ontogeny. As further endogenous ligands are proposed, this line can be used to screen for safety and efficacy and can report on the ability of small molecules to regulate critical cellular processes by modulating the activity of the AHR.